A Critical Analysis and Evaluation of Requirement Prioritization using Analytical Hierarchy Process (International Journal of Engineering and Computer Science, 2017)
Requirement engineering is the important phase of the software development life cycle. The objective of requirement engineering is to discover and collect the requirements from the client environment. The requirement engineer performs the critical role in examining and prioritize the requirements based on its necessity and feasibility. The requirement engineering makes complex decisions about the requirements in software development process. Selecting and prioritizing the proper requirement from the multiple is critical task. The Analytical Hierarchy process (AHP) is a multi criteria decision making method provides an effective quantitative approach for prioritizing the requirements. The objective of the paper is to evaluate the prioritization of requirements based on feasibility using the AHP.